Biology of the European oak borer in Michigan, United States of America, with comparisons to the native twolined chestnut borer. Issue 1 (15th November 2013) - Petrice, Toby R.; Haack, Robert A.
Abstract: In 2010–2011, we studied the European oak borer (EOB), Agrilus sulcicollis Lacordaire (Coleoptera: Buprestidae), in Michigan, United States of America, and made comparisons with the native twolined chestnut borer (TLCB), Agrilus bilineatus (Weber). EOB adult flight began and peaked before TLCB. More EOB females were captured on purple and white compared with yellow and green sticky traps. More TLCB females were captured on purple, followed by yellow, green, and white, respectively. Male EOB and TLCB did not show a significant colour preference. EOB completed development primarily from areas of artificially girdled trees where the phloem had died soon after trees were girdled, while TLCB usually developed in areas of girdled trees that had some live phloem present. Both EOB and TLCB successfully attacked and emerged from girdled Quercus alba Linnaeus, Quercus robur Linnaeus, and Quercus rubra Linnaeus (Fagaceae) trees. No live EOB or TLCB were found in two ungirdled and apparently healthy Q. robur trees that were dissected. EOB attacked and emerged from Q. alba, Q. robur, Q. rubra, and Quercus velutina Lamarck trap logs. Differences in the pronotal groove and terminal processes can be used to distinguish EOB from TLCB larvae. Five species of parasitoids were reared from EOB and four from TLCB. Résumé: Nous avons étudié en 2010–2011 l'agrile européen du chêne (EOB), Agrilus sulcicollis Lacordaire (Coleoptera: Buprestidae), au Michigan, États-Unis d'Amérique, et l'avons comparé à l'agrile du châtaignier (TLCB), Agrilus bilineatus (Weber), une espèce indigène. La période de vol de EOB débute et atteint son sommet avant celle de TLCB. Plus de femelles EOB ont été capturées sur des pièges collants violets et blancs que sur des pièges jaunes et verts. Le plus grand nombre de femelles TLCB a été capturé sur des pièges violets, puis par ordre sur des jaunes, des verts et des blancs. Les mâles EOB et TLCB ne montrent aucune préférence significative de couleur. Les EOB complètent leur développement principalement dans des zones d'arbres annelés artificiellement chez lesquels le phloème est mort peu après l'annélation des arbres, alors que les TLCB se développement généralement dans des zones d'arbres annelés chez lesquels il reste du phloème vivant. Tant les EOB que les TLCB attaquent avec succès les chênes Quercus alba Linnaeus, Q. robur Linnaeus et Q. rubra Linnaeus (Fagaceae) annelés et en émergent. Aucun EOB ni TLCB vivant n'a été trouvé lors de la dissection de deux chênes Q. robur non annelés et à apparence saine. Les EOB attaquent les billes de chênes Q. alba, Q. robur, Q. rubra et Q. velutina Lamarck utilisées comme pièges (trap logs) et en émergent. Des différences dans le sillon du pronotum et des processus terminaux peuvent servir à distinguer les larves de EOB et de TLCB. Cinq espèces de parasitoïdes ont été obtenues par élevage de EOB et quatre de TLCB.